If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16y + -13 = 72 + -14y Reorder the terms: -13 + 16y = 72 + -14y Solving -13 + 16y = 72 + -14y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '14y' to each side of the equation. -13 + 16y + 14y = 72 + -14y + 14y Combine like terms: 16y + 14y = 30y -13 + 30y = 72 + -14y + 14y Combine like terms: -14y + 14y = 0 -13 + 30y = 72 + 0 -13 + 30y = 72 Add '13' to each side of the equation. -13 + 13 + 30y = 72 + 13 Combine like terms: -13 + 13 = 0 0 + 30y = 72 + 13 30y = 72 + 13 Combine like terms: 72 + 13 = 85 30y = 85 Divide each side by '30'. y = 2.833333333 Simplifying y = 2.833333333
| -32-3x=2(2+8x)-x | | 6*2+3y=15 | | -8v-3=-5v+3 | | 3y+(15x+75)=180 | | -5y(x-3)=-25 | | x(x+3)=9 | | -2(2x-1)+3=9 | | 5-2p= | | 5x-5=3x+13 | | 12a+12+5a-9= | | 8a=860 | | 9w-17.9=-2.3 | | x^3-16x^2-216x+896=0 | | z=9y+3yx | | 2(-2x-1)+3=9 | | 4-5(1-4m)=-121 | | (5+i)(8+I)= | | 1+8x=-9+x-1-3 | | 2/3g=9/2 | | 19x=7(x+3y) | | 6xX=90 | | 2/3g=4.5 | | 23g=4.5 | | 3x+9-6(x+1)=6x+5 | | -8(-5m+2)=-96 | | 23g=41/2 | | 4(n-6)+10=2(n-7)-6 | | -14+3(x+10)=7(2+4)+x | | 33+3x+11x=33x | | 6+2x=3x+7+1-8 | | 5(12-3p)=1215p+60 | | -2(6-y)+4=-4 |